FUNCTIONAL AND RADIOLOGICAL OUTCOME OF HOOK PLATE FIXATION IN DISPLACED LATERAL END CLAVICLE FRACTURES: A PROSPECTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Displaced lateral end clavicle fractures are unstable injuries with a higher risk of delayed union, non-union and shoulder dysfunction when treated conservatively. Hook plate fixation provides stable fixation, especially when the distal fragment is small or comminuted. Methods: This prospective observational study was conducted in the Department of Orthopaedics, SMS Medical College and Attached Hospitals, Jaipur. A total of 34 adult patients with displaced lateral end clavicle fractures underwent open reduction and internal fixation using a clavicular hook plate. Patients were assessed clinically and radiologically during follow-up. Functional outcome was evaluated using the Constant-Murley score, while radiological outcome was assessed by fracture union and maintenance of reduction. Results: The mean age of patients was 38.7 ± 10.4 years, and 73.5% were males. Road traffic accident was the most common mode of injury. Mean VAS score reduced from 8.0 ± 0.8 preoperatively to 0.8 ± 0.4 at 6 months. Mean Constant-Murley score improved to 89.6 ± 5.8 at final follow-up. Radiological union was achieved in all patients, with mean union time of 12.1 ± 1.2 weeks. Conclusion: Hook plate fixation is an effective option for displaced lateral end clavicle fractures, providing reliable union, pain relief and good functional recovery.